Pola konsumsi minuman es dan kepedulian terhadap keamanan pangan di Kota Bogor - Winiati Pudji Rahayu; Siti Nurjanah; Sophia Ekaristi Dharma Gita (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Consumption pattern of iced beverages of the consumer in Bogor and their awareness of food safetyBackground: Iced beverage will be potentially contaminated by microbes if it is prepared and handled by a lack of sanitary and hygiene. The level of risk depends on exposure affected by the prevalence and concentration of microorganisms, also the consumption patterns.Objective: The objective of this study was to determine the iced beverages consumption number in Bogor using a semi-quantitative food frequency questionnaire (SQ-FFQ) and to know the level of knowledge and awareness of food safety.Method: The survey used 300 respondents, including males and females, which classified in three groups of age and three groups of income level also the final level of education.Results: Most of the respondents were frequently consumed flavored iced beverages (52%) compared to other types of iced beverages and the average number of daily consumption was 182 mL/person. Based on compare means analysis, the amount of iced beverages consumption was not affected by age and gender but was influenced by income. The level of knowledge and awareness of food safety of consumers in Bogor was good (>80%). Based on Chi-Square analysis, the level of knowledge and awareness of consumers were not affected by age, gender, or final education. However, when viewed from the percentage of correct answers, the main factor of the level of knowledge and awareness of consumers was the final level of education.Conclusion: The amount of iced beverages consumption was not affected by age and gender but influenced by income, and the average consumption was 135 mL/person/day. The level of knowledge and awareness of food safety of consumers in Bogor was good (>80%).